2008
DOI: 10.1177/0363546508315471
|View full text |Cite
|
Sign up to set email alerts
|

High Tibial Osteotomy for Unloading Osteochondral Defects in the Medial Compartment of the Knee

Abstract: This loading situation most closely approximates physiologic loading and therefore represents an ideal outcome for patients with isolated chondral defects. Reduction in stress concentration around chondral defects has been found to favor cartilage repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
108
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(120 citation statements)
references
References 26 publications
9
108
0
3
Order By: Relevance
“…The mean mechanical leg axis in this patient group was in accordance with the recommended valgus leg alignment post-HTO 40,41 . The mean change in femorotibial angle was 10 which seems to be large enough to expect significant changes in cartilage loading patterns represented in the dGEMRIC measurements.…”
Section: Discussionsupporting
confidence: 75%
“…The mean mechanical leg axis in this patient group was in accordance with the recommended valgus leg alignment post-HTO 40,41 . The mean change in femorotibial angle was 10 which seems to be large enough to expect significant changes in cartilage loading patterns represented in the dGEMRIC measurements.…”
Section: Discussionsupporting
confidence: 75%
“…This treatment algorithm is consistent with biomechanical data, which show an equal load distribution between the medial and lateral compartment on cadaveric knees between 0° and 4° of valgus [24]. There are no data available about the amount of varus deviation that can be tolerated in case of osteochondral resurfacing.…”
Section: Discussionsupporting
confidence: 82%
“…Recent biomechanical work has shown that the medial compartment is completely unloaded with correction to between 6° and 10° of anatomic valgus and that the load is equalized between the medial and lateral compartments, with correction to between 0° and 4° of anatomic valgus. The study's authors recommended from these biomechanical data that treatment for varus gonarthrosis be overcorrection of the mechanical axis and that treatment for isolated medial femoral condyle chondral injuries involves only correction to physiologic alignment as opposed to overcorrection [ 13 ]. The fi rst step is to draw the mechanical axis line from the center of the femoral head to the center of the talus.…”
Section: Preoperative Planningmentioning
confidence: 99%